Compósitos de nanocelulose / PHBV: manta microfibrilica por eletrofiação - Benini, Kelly Cristina Coelho de Carvalho [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The production of nanobiocomposites has grown in recent years considering the need to develop materials to replace those produced using raw materials derived from petroleum and that take a long time to degrade, damaging the environment. However, nanobiocomposites of PHBV/cellulose nanocrystals (CNC), were obtained by solvent casting and electrospinning. First of all, was determined the best sequence of chemical treatments to obtain cellulose from brazilian satintail, and the conditions were: alkali treatment with NaOH solution (5% w/w) at 75°C , followed by three stages of bleaching with H2O2/NaOH. Then, following a design of experiments (DOE) it was possible to determine the best conditions of acid hydrolysis to obtain the CNC: H2SO4 60% (w/w) at 60°C for 30 min (CNC4) and H2SO4 64% (w/w) at 35°C for 75 min (CNC9). Afterwards, other DOE was conducted to determine the most appropriate PHBV solubility and processing parameters, and the results obtained led to the choice of the following parameters: PHBV solution containing 5% (w/w) of polymer in solvent dimethylformamide and chloroform (ratio 22/78), solubilized at 50°C for 30h; casting at 153°C, and electrospinning with needle (20x10), drum rotation of 27 rpm, working distance of 10 cm and environmental conditions close to 25°C and 50% of moisture. Finally, the nanocomposites PHBV/NCC4 and PHBV/NCC9 were obtained with the addition of 1% (w/w) of reinforcement by casting and electrospinning process, following the solubility and processing conditions determined at DOE. The addition of CNC in the nanocomposites obtained by solvent casting did not change the transparency of the films and provided a significant decrease in the polymer crystallization temperature, mainly with the addition of CNC4, whereas for electrospun nanocomposites, provided a considerable improvement in process efficiency, by ... (Complete abstract click electronic access below)

A produção de nanobiocompósitos tem crescido nos últimos anos considerando a necessidade no desenvolvimento de materiais que visam substituir aqueles produzidos com matéria-prima oriunda do petróleo e que demoram muito tempo para se degradarem, prejudicando o meio ambiente. Dentro deste contexto, foram confeccionados nanobiocompósitos de PHBV/nanocristais de celulose (NCC) por casting e eletrofiação. O desenvolvimento do trabalho consistiu inicialmente na determinação da melhor sequência de tratamentos químicos para a obtenção da celulose a partir do capim-sapê, e as condições determinadas foram: tratamento alcalino com solução de NaOH 5% (m/m), a 75°C, seguido por três etapas de branqueamento com H2O2/NaOH. Em seguida, foi realizado um planejamento de experimentos (PE) com o qual foi possível determinar as melhores condições de hidrólise ácida para a obtenção dos NCC, que foram: H2SO4 60% (m/m), a 60°C por 30 min (NCC4) e H2SO4 64% (m/m), a 35°C por 75 min (NCC9). Posteriormente, outro PE foi realizado para determinar os parâmetros mais adequados para a solubilidade e processamento do PHBV, e os resultados obtidos levaram à escolha dos seguintes parâmetros: solução de PHBV com 5% (m/m) de polímero em solventes dimetilformamida e clorofórmio (razão 22/78) solubilizados a 50°C por 30h, casting a 153°C e eletrofiação com agulha 20x10, rotação do tambor de 27 rpm, distância de trabalho de 10 cm, com condições ambientais próximas a 25°C e 50% de umidade. Por fim, foram confecionados os nanocompósitos PHBV/NCC4 e PHBV/NCC9, com a adição de 1% (m/m) de reforço, pelos processos de casting e eletrofiação, seguindo as condições de solubilidade e processamento estabelecidas no PE. A adição dos NCC nos nanocompósitos obtidos por casting não alterou a transparência dos filmes e proporcionou uma redução ... (Resumo completo, clicar acesso eletrônico abaixo)
Nanocellulose/PHBV composites: microfibilated mats by electrospinning
Keywords: Materiais compostos; Fibras; Celulose; Materiais nanoestruturados; Solubilidade; Compostos fibrosos; Composite materials